Contextual Learning on Type 2 Diabetes Mellitus Based on Case Studies: Educational Media Innovation in Science Learning in Senior High Schools - Muhammad Syahrir; Dewi Rahayu; T. Khairol Razi; Muzakir Muhammad Amin; Sulaiman; Flora Eka Sari (Postgraduate, University of Mataram, 2025)
In the context of science learning, the application of a contextual approach becomes increasingly relevant when learning themes are integrated with public health issues, one of which is Type 2 Diabetes Mellitus (T2DM), which has become a serious concern in recent years both nationally and globally. This study aims to develop and test the effectiveness of case study-based educational media on Type 2 Diabetes Mellitus in science learning at SMA Negeri 1 Luwuk, Banggai Regency, Central Sulawesi. The media was designed using a contextual learning approach (Contextual Teaching and Learning/CTL) and packaged in the form of interactive visual narratives relevant to the lives of adolescents. The study used the Research and Development (R&D) method with grade XI students as subjects and involved the principal and science teachers as supporting data sources. The instruments used included validation sheets, pretest–posttest questions, and interview and observation guidelines. The validation results showed the media was categorized as very feasible. Limited trials showed a significant increase in student learning outcomes, with a gain value of 0.57 (medium–high category). In addition, students showed emotional involvement and increased awareness of the importance of a healthy lifestyle. Teachers and the principal responded positively to the media's usefulness in supporting active and meaningful learning.